2014
DOI: 10.1177/039463201402700111
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles and Hepatic Injury in Occult Hepatitis C Versus Chronic Hepatitis C Virus Infection

Abstract: Occult hepatitis C virus (HCV) infection is a new entity that should be considered when diagnosing patients with abnormal liver functions of unknown origin. This work was carried out to evaluate T-helper liT-helper 2 (Thl/Th2) cytokine profiles in patients with occult HCV infection versus chronic hepatitis C (CHC) infection, also to investigate any association between theses cytokines and liver histological features in both groups. Serum levels of Thl cytokines (IL-2, IFN-y) and Th2 (IL-4 and IL-IO) were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…The cytokine balance between Th1/Th2 may also be a factor in the development of OCI cases [ 77 , 84 89 ]. Mousa et al [ 87 ] investigated the role of cytokine profiles including cytokines related to T-cell immunoregulation in the development of OCI. They compared the cytokines responses between OCI and those with an identifiable chronic hepatitis C infection (CHC).…”
Section: Potential Pathogenic Mechanisms Resulting In An Oci ( mentioning
confidence: 99%
“…The cytokine balance between Th1/Th2 may also be a factor in the development of OCI cases [ 77 , 84 89 ]. Mousa et al [ 87 ] investigated the role of cytokine profiles including cytokines related to T-cell immunoregulation in the development of OCI. They compared the cytokines responses between OCI and those with an identifiable chronic hepatitis C infection (CHC).…”
Section: Potential Pathogenic Mechanisms Resulting In An Oci ( mentioning
confidence: 99%
“…Similar results were described by Mousa et al, who revealed that Th1-type cytokines were significantly increased in patients with CHC relative to OCI but that the serum IL-4 levels as a Th2-type cytokine were higher in OCI. The serum IL-10 levels were high in both groups, with no significant difference between CHC and occult HCV groups ( 71 ). In light of these studies, we believe that perturbation of the immune response balance toward Th2-type cytokines plays a role in the clinical scenario of OCI, causing the virus to persist with fewer manifestations than CHC.…”
Section: Immune Responsesmentioning
confidence: 99%
“…On the other hand, individuals with an OCI had higher serum IL-4 levels than in CHC and the healthy controls. Serum levels of IL-10 were higher in both OCI and CHC groups compared with control (Mousa et al, 2014).…”
Section: Potential Pathogenic Mechanisms Resulting In An Ocimentioning
confidence: 77%
“…The cytokine balance between Th1/Th2 may be an important factor in the development of OCI cases (Gad et al, 2012;Mousa et al, 2014).…”
Section: Potential Pathogenic Mechanisms Resulting In An Ocimentioning
confidence: 99%